We are in the Same Boat: Group Therapy as a Treatment for Psychological Distress in Dating Violence Survivors - Pradipta Christy Pratiwi; Fatma Kusuma Mahanani; Tri Esti Budiningsih; Julian Adrian Halim (Journal of Educational, Health and Community Psychology, 2022)
Young adults are synonymous with the task of developing intimacy. This phase is inseparable from the problem of dating violence. This situation is a social stressor that causes a negative stress response commonly known as psychological distress. The purpose of this study is to provide treatment for 5 young adults who have experienced dating violence with online group intervention. The intervention design was carried out for seven 60-90 minutes sessions. The evaluation was done using observation, DASS, and BDI-II. Friedman’s test showed a significant result for depression (BDI-II, χ2F = 6.533, p = .038; DASS, χ2F = 6.533, p = .038) and anxiety (χ2F = 6.000, p = .050), and a non-significant result for stress (χ2F = 3.500, p = .174).